The Finnish line - Rest, J. (Sportcal Insight, 2015)
Between 2000 and 2014, over 150 international sports events were held in Finland, and that appetite shows no sign of abating over the next three years as the Nordic country nears a historic landmark. Helsinki, Finland's capital, was a star performer in the recent edition of Sportcal's Global Sports City Index, rising 11 places to 17th. Meanwhile, Finland itself has been making strides in the Nations Index over the past few years, now sitting 23rd in the table for the period 2009 to 2020. And the future looks even brighter. For the future 2015-2020 cycle, Finland is up to 17th in the table, thanks to an expanding portfolio of major events heavily focused on 2017, the centenary of Finland's independence. Sport will play a key role in the celebrations through the work of Finland 100, a secretariat that is organising the centenary celebrations, and Sport Finland, a unit of the Finnish Olympic Committee that works with seven cities (Helsinki, Lahti, Tampere, Turku, Kuopio, Oulu and Jyvaskyla) to co-ordinate bidding for and hosting of events. With 302 medals, Finland is the most successful nation at the Olympics in terms of medals per capita (one medal per 17,904 people), and Kati Malkki, special adviser at Sport Finland, says it was the success of the country's Olympic athletes that "helped put Finland on the world map." She says: "Sport helped shape our national identity, so it makes sense that it plays a role in such a big year for the country. We'll have a full year of sports events from January leading up to 6 December (Independence Day) - not just major championships but also small events that have strong links to Finland."